2010
DOI: 10.1002/aic.12161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of column diameter and bed height on minimum fluidization velocity

Abstract: Experiments show that the minimum fluidization velocity of particles increases as the diameter of the fluidization column is reduced, or if the height of the bed is increased. These trends are shown to be due to the influence of the wall. A new, semicorrelated model is proposed, which incorporates Janssen's wall effects in the calculation of the minimum fluidization velocity. The wall friction opposes not only the bed weight but also the drag force acting on the particles during fluidization. The enhanced wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…In addition, it is noted that for 104 μm solid particles ( D h / d p = 96.15), U mf,e is slightly higher than U mf,t , which indicates that the friction stress still exits and influences U mf even for higher D h / d p (96.15). Rao et al also found that the wall effect affected the fluidization characteristic when D h / d p was up to 150 in a 16 mm bed.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, it is noted that for 104 μm solid particles ( D h / d p = 96.15), U mf,e is slightly higher than U mf,t , which indicates that the friction stress still exits and influences U mf even for higher D h / d p (96.15). Rao et al also found that the wall effect affected the fluidization characteristic when D h / d p was up to 150 in a 16 mm bed.…”
Section: Resultsmentioning
confidence: 95%
“…In macroscale three‐phase fluidized beds, the static bed height scarcely affects U Lmf , which can be seen from many formulas for predicting U Lmf . However, the static bed height exerts a greater influence on the minimum fluidization velocity for the liquid‐solid or gas ‐solid systems at a smaller bed diameter . Figure shows the effect of the static bed height on U Lmf for gas‐liquid‐solid MFB with bed diameter of 10 mm of 740 μm solid particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure illustrates the effect of H 0 on U MF , and it shows that the U MF decreases with an increase in the H 0 . On one hand, the U MF increases as the H 0 is increased, which is due to the larger resistance of wall in the DTSFB, making it more difficult to fluidize the particles . On the other hand, the resistance of the annular region increases with the increase in H 0 , which prevents the spouting gas bypass in the annular region, resulting in a decrease in U MF .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, minimum fluidizing velocity has been studied in a fluidized bed as an important parameter . Some of the literature proposed correlations for predicting the minimum fluidizing velocity in fluidized beds, and Moradi et al studied the effect of the geometry of a spouted bed on the minimum fluidization velocity numerically, which was calculated based on the volume fraction distribution comparison.…”
Section: Introductionmentioning
confidence: 99%